ANALISIS MEDAN MAKNA DALAM HR. IMAM BUKHARI NO. 4700 TENTANG ANJURAN MEMILIH PASANGAN DALAM ISLAM - Amalia, Rifda; Hidayah, Nurul; Sholahuddin, Muhammad Faishol (Al Tadib : Jurnal Ilmu Pendidikan, 2023)
The field of meaning can be understood as a group of words that present a series of interrelated meanings. Every process of understanding the meaning of words requires accuracy to understand the meaning before and after it. Hadits is one of the things that is urgent to study the field of its meaning so that humans understand matan in depth. Specifically in HR. Imam Bukhari No. 7400 regarding recommendations for choosing a partner in Islam. The author describes the purpose of this research: (1) to describe the field of meaning in HR. Imam Bukhari No. 7400 regarding recommendations for choosing a partner in Islam (2) Describe the essence of HR. Imam Bukhari No. 7400 regarding recommendations for choosing a partner in Islam. The method used in gathering information to present valid data is to use a qualitative research method with analytic descriptive type. Meanwhile, the hadith research techniques use the tashih method, the takhrij method, the tahlili method, the takwil method, and the tathbiq method. Researchers can present results by drawing conclusions (1) the meaning field of HR. Imam Bukhari No. 7400 regarding recommendations for choosing a partner in Islam, there are interrelated meanings and there are also several sentences containing fi'il mudhori 'mabni li al-majhul, naib al-fa'il, and so on (2) according to HR. Imam Bukhari No. 7400 that in Islam choosing a partner there are four aspects that are the most important factors in a household, namely wealth, lineage, beauty, and strong religion. Keywords: Field of Meaning, HR. Imam Bukhari No. 7400, Advice for Choosing a Partner.